'For My Descendants and Myself, a Nice and Pleasant Abode' – Agency, Micro-history and Built Environment : Buildings in Society International BISI III, Stockholm 2017 /: Buildings in Society International BISI III, Stockholm 2017. (2020) - Unknown
No abstract available